PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS DAN HASIL BELAJAR BIOLOGI SISWA KELAS VIII-6 SMP NEGERI 1 TEBING TINGGI - Saria Sinaga (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2020)
The purpose of this study was to improve science process skills and biology learning outcomes of students in grades VIII - 6 SMP Negeri 1 Kota Tebing Tinggi. The type of research used is Classroom Action Research (PTK). This research was conducted in two cycles. To obtain research data, data collection was carried out using qualitative descriptive analysis techniques to determine science process skills and student learning outcomes. The results showed that with the application of the Discovery Learning learning model to improve science process skills and student learning outcomes with the total score obtained in the first cycle of students' science process skills with a percentage of 66%, cycle II increased to 86.66% while learning outcomes which is obtained by students as seen from the average value and value of classical completeness of student learning as follows: by percentage, the average value in the first cycle is 54.40%, the second cycle is 72.40%. While the percentage of classical completeness in the first cycle was 52%, the second cycle was 80%. Thus, the use of the Discovery Learning Learning Model can be recommended to be applied as an alternative learning model in schools.Keywords: Discovery Learning, Skills, Learning Outcomes